Watercolour - Monahan, Patricia (London, United Kingdom : Hamlyn Publishing Group Limited, 1987)
Watercolor has a fresh,glowing translucency which many artist, including beginners, find irresistible. It is a demanding, irritating but fascinating medium. It is also full of contradictions, for though undoubtedly a difficult medium to master, the basic techniques are really very simple.
Introduction -- 2. Equipment -- 3. Washes: Techniques ; Rain clouds 1 ; Rain clouds 2 ; The beach -- 4. Further Techniques ; Techniques ; Country track ; Mil in water ; Child with panda ; House by the shore -- 5. Masking ; Techniques; Summer fields; Sailing in the bay; Town gate; Anemones -- 6. Approaches ; Techniques ; On the beach ; Boats - low tide ; Still life - Shells ; Rocky headland ; Daffodils ; Buttercups in a blue vase -- Glossary -- Index.
Includes index.
Keywords: WATERCOLOR PAINTING